2018
DOI: 10.1002/jmv.25375
|View full text |Cite
|
Sign up to set email alerts
|

Response of hepatitis B virus to antiretroviral treatment containing lamivudine in HBsAg‐positive and HBsAg‐negative HIV‐positive South African adults

Abstract: Both hepatitis B virus (HBV) and human immunodeficiency virus (HIV) infection are highly endemic in sub‐Saharan Africa. This study examined serological and clinical follow‐up data from 39 HBV DNA‐positive, HIV‐positive black South African adults, who returned for follow‐up at 3, 6, 12, and 18 months post‐initiation of antiretroviral therapy (ART). Of the 39 participants, 10 experienced full suppression of HBV and 29 experienced no suppression, with 10 of these showing a virological breakthrough. All 10 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Studies using samples from lamivudine-treated or -naïve SA patients with CHB reported reverse transcriptase gene mutations in 75.6% of isolates from patients receiving lamivudine, and 38% of cases were associated with drug resistance and treatment failure [28]. Interestingly, lamivudine resistance mutations were also detected in 37% of lamivudine-naïve patients [28,29] and in HIV/HBV co-infected individuals [30,31]. The resistance-associated mutations detected from lamivudine-naïve patients were likely to be polymorphisms of the wild-type viral sequence [32].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using samples from lamivudine-treated or -naïve SA patients with CHB reported reverse transcriptase gene mutations in 75.6% of isolates from patients receiving lamivudine, and 38% of cases were associated with drug resistance and treatment failure [28]. Interestingly, lamivudine resistance mutations were also detected in 37% of lamivudine-naïve patients [28,29] and in HIV/HBV co-infected individuals [30,31]. The resistance-associated mutations detected from lamivudine-naïve patients were likely to be polymorphisms of the wild-type viral sequence [32].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies on the impact of HBV/HIV coinfection in natural disease progression were carried out in the HBsAg-positive individuals as in the studies described above. In contrast, there is a paucity of data on OBI natural disease progression owing to the few longitudinal studies on OBI, especially in Africa, where different genotypes/subgenotypes of HBV and subtypes of HIV circulate ( Amponsah-Dacosta et al, 2018 ; Singh et al, 2019 ). A study in China followed seven OBI-positive blood donors, and all were HBV DNA negative at 1-year follow-up, without an intervention ( Ye et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%